Deformation Influencing Factor Analysis for Shield Tunnelling under Micro-shallow Gas Strata - YANG Xin; HONG Yi; WANG Lizhong (Chengshi guidao jiaotong yanjiu)
[Objective] Shallow gas stratum is widely distributed in coastal areas of China, affecting the safety of subway tunnel construction. Therefore, it is necessary to deeply study the factors influencing deformation of shield tunneling through shallow gas stratum. [Method] Relying on the shield tunnel project of Hangzhou Metro Line 1 crossing under Xiao-shan Airport, the buried depth and peak gas pressure distribution of shallow gas strata in the shield section are analyzed through the results of the advanced gas releasing project near Xiaoshan Airport. Based on triaxial undrained unloading test of saturated soil and gas-bearing soil, as well as the numerical simulation results, the excavation risks of shield construction in micro-shallow gas strata are analyzed, and risk control factors are proposed. A typical monitoring section is selected to analyze the relationship between land subsidence and shield construction process, determining the boundary values of stratum loss settlement and consolidation settlement during shield tunnel construction in gas-bearing soft soil strata. The importance of shield tunneling parameters on land subsidence during shield construction in gas-bearing soil layers is analyzed based on a random forest model. [Result & Conclusion] The buried depth of the shallow gas-rich layer in the shield section ranges is from 20 m to 30 m, with a peak gas pressure of approximately 0.01 MPa, indicating a micro-shallow gas layer. During shield construction crossing gas-bearing strata, special attentions should be paid to the pressure control in the earth chamber to reduce the risks of liquefaction instability and stratum collapse in the gas-bearing soil at the excavation face. When excavating in gas-bearing strata, the stratum loss settlement and consolidation settlement should be distinguished 2 to 3 days later after the shield tail has left. The importance ranking of shield tunneling parameters affecting land subsidence is as follows: earth chamber pressure, torque, grouting volume, thrust, soil discharge volume, and advancing speed.